Write an equivalent expression to the problem in the picture
![Write an equivalent expression to the problem in the picture class=](https://us-static.z-dn.net/files/d06/fd30d48ef44e06223c65e0cbf5f8b43d.png)
Answer:
An equivalent expression to the given expression is;
[tex]6-m=114[/tex]Explanation:
Given the equation;
[tex]-\frac{1}{2}m+3=57[/tex]we want to write an equavalent expression to the above;
let us multiply through by 2;
[tex]\begin{gathered} -\frac{1}{2}m+3=57 \\ -\frac{1}{2}m(2)+3(2)=57(2) \\ -m+6=114 \\ 6-m=114 \end{gathered}[/tex]Therefore, an equivalent expression to the given expression is;
[tex]6-m=114[/tex]